A Framework of Building and Locational Characteristics Ranking for Purpose-built Offices in Malaysia - Mohd, Edie Ezwan (Journal of Education and Vocational Research, 2013)
The development of purpose-built office market in Malaysia is primarily resolved by a supplydemand market. Since the office market in Malaysia has displayed significance improvement due to increasing level of competitiveness, many characteristics of purpose-built office have appeared and become prominent during the process of assessment. These characteristics were generally used as indicators in property valuation, building performance as well as office market appraisal. Based on these characteristics, property market participants can evaluate their property proficiently based on their requirements, especially in decision making during business planning, investment or property management. Technology growth and national policy also gave contribution factors on revealing newly characteristics of purpose-built office such as green building, intelligent building and sustainable development model. The purpose of this article is to identify suitable characteristics of purpose-built office that can be used in Malaysia. Integral to achieving this objective, exploration on purpose built office characteristics in a global and local context will be reconsidered. As a result, a building and locational framework of purpose-built office’s characteristics in Malaysia will be diagnosed and verified appropriately.